Problematika Hukum Perkawinan Usia Dini Bagi Kehidupan Perempuan - Nurkasim, Nurkasim; Khaliq, Achmad; Cahyani, Dewi (Syekh Ali Hasan Ahmad Addary State Islamic University, 2025)
Child marriage refers to a marital union conducted at an early age, in which individuals—particularly adolescents—are not yet adequately prepared to enter into such a significant life commitment. Nevertheless, due to specific underlying reasons, such marriages are sometimes carried out in an effort to avoid greater harm or societal repercussions. Law No. 1 of 1974 also regulates the minimum age requirement for marriage for both males and females, with the aim of establishing a stable and enduring family, consistent with the ultimate goals of marriage. In practice, child marriages often experience disharmony within the family structure, primarily due to the couple’s lack of readiness to bear the burdens of life and assume the responsibilities of parenthood. Consequently, such marriages are highly susceptible to ending in divorce. This study employs a qualitative descriptive approach, which seeks to portray the social realities surrounding the issue. Data were collected through interviews. The findings of this study reveal that underage marriages often occur despite couples lacking sufficient maturity and violating legal marriage requirements as stated in Chapter II of the Marriage Law. In Kasokandel, Argapura, and Majalengka districts, underage couples frequently experience marital disharmony due to unmet spousal rights and obligations, infidelity, and recurring conflicts, often leading to divorce. Child marriage negatively impacts household harmony, as young spouses generally face adverse consequences stemming from psychological unpreparedness to handle the challenges of married life, which ultimately diminishes family quality.